Princípios de redução das fraturas panfaciais: revisão de literatura - Correa, Ana Paula Simoes [UNESP]; Mello, Regis Alexandre [UNESP]; Pellizzer, Eduardo Piza [UNESP] (My University, 2013)
Are called panfacial fractures when the upper, middle and lower facial thirds present fractures concurrently. In clinical practice, came to imply the involvement of two facial thirds. Panfacial fractures are usually accompanied by other systemic lesions that impair the patient's life and therefore require primary treatment. Almost invariably are associated with damage to soft tissues and severe losses of bone structures which may lead to severe facial deformations and malocclusions. The panfacial fractures treatment is complex because often there isn’t a stable bone structure to guide the reduction of various fractures. Several orders of treatment have been proposed, but they are variations of the two classical approaches "bottom to top and inside-out" and "top to bottom and out-inside". The aim of this paper is to discuss the principles of management and panfacial fractures treatment, emphasizing the sequence of fracture reduction and highlighting its indications, advantages and disadvantages, through literature review and reports of surgical clinic cases. We conclude that the exact sequence of fracture reduction is not as important as developing a treatment plan that allows accurate positioning of the fractured segments.

As fraturas panfaciais recebem essa denominação quando todos os terços faciais apresentam fraturas concomitantes. Na prática clínica, passou a implicar no envolvimento de dois terços faciais. As fraturas múltiplas geralmente estão associadas a outras lesões sistêmicas, que necessitam de tratamento primário. Quase que com freqüência essas lesões estão relacionadas aos tecidos moles e perdas de estruturas ósseas severas que podem levar a graves deformidades faciais e maloclusão. Devido a ausência de estruturas óssea estáveis, as quais sirvam de arcabouço para a redução das fraturas, esse tratamento é considerado complexo. Sendo assim, várias formas de tratamento vêm sendo propostas, contudo todas são variações das duas abordagens clássicas “de baixo para cima e de dentro para fora” e “de cima para baixo e de fora para dentro”. O objetivo aqui é discutir os princípios de redução das fraturas panfaciais, dando ênfase a seqüência de abordagens de redução das fraturas e enfatizando suas indicações, vantagens e desvantagens, por meio da revista da literatura. Conclui-se que a sequência de redução das fraturas não é tão importante quanto o desenvolvimento de um plano de tratamento que permita o posicionamento adequado dos segmentos fraturados.
Principles for reducing panfacial fractures: literature review
Keywords: Multiple traumatism; Dental occlusion e treatment; Traumatismo múltiplo; Oclusão dentária e tratamento